ERK signaling for cell migration and invasion - Samson, Shiela C.; Khan, Akib M.; Mendoza, Michelle C. (Frontiers in Molecular Biosciences, 2022)
The RAS - Extracellular signal-regulated kinase (RAS-ERK) pathway plays a conserved role in promoting cell migration and invasion. Growth factors, adhesion, and oncogenes activate ERK. While historically studied with respect to its control of cell proliferation and differentiation, the signaling pattern and effectors specific for cell migration are now coming to light. New advances in pathway probes have revealed how ERK activity is transmitted for collective migration and how ERK induces actin, adhesion, and myosin activity for forward cell motion. Amongst the puzzling myriad of ERK effectors, the key players in edge protrusion and cell body contraction are now realized. Here, we review how sustained ERK pathway stimulation generates waves of ERK activity that drive actin polymerization, adhesion turnover, and cell contraction for cell migration and invasion.